Wicked river [compact disc, unabridged] : a novel - Milchman, Jenny (Dreamscape Media, LLC, 2018)
An isolated backcountry honeymoon seemed ideal, until Natalie and Doug realized they weren't alone in the woods, and that they may never be able to leave.